Faktor-Faktor yang Mempengaruhi Niat Pembelian Kendaraan Listrik di Indonesia: Sebuah Tinjauan Literatur Sistematis - Muhamad Nurbudiansyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The transition to electric vehicles (EVs) has become a key element in the global sustainability agenda, including in Indonesia. This study aims to systematically identify and synthesize the factors influencing consumers’ purchase intention of electric vehicles in Indonesia based on previous research. The method employed is a Systematic Literature Review (SLR) of ten national academic articles published between 2020 and 2025. The selection process was based on inclusion criteria related to the Indonesian context, focus on purchase intention, and the application of theoretical approaches such as the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM). The review identifies four main categories of factors affecting EV purchase intention: economic, psychological, social, and policy-related. Among these, economic factors—particularly price and incentives—are the most dominant, followed by attitude, perceived behavioral control, and social influence. This study contributes to the formulation of promotional strategies, public policy, and future research directions grounded in the Indonesian context.